Psychopathic Personality Traits Scale (PPTS): Construct Validity of the Instrument in a Sample of U.S. Prisoners - Boduszek, Daniel; Debowska, Agata; Sherretts, Nicole; Willmott, Dominic (Frontiers in Psychology, 2018)
The Psychopathic Personality Traits Scale (PPTS; Boduszek et al., 2016) is a personality-based psychopathy assessment tool consisting of four subscales: affective responsiveness, cognitive responsiveness, interpersonal manipulation, and egocentricity. Although the measure offers a promising alternative to other, more behaviorally weighted scales, to date the factor structure of the PPTS and differential predictive validity of its dimensions has only been tested in one study. Consequently, the objective of the present research was to assess construct validity, factor structure, and composite reliability of the PPTS within a sample of U.S. male and female incarcerated offenders (N = 772). Another goal was to test the predictive efficiency of the PPTS dimensions for different types of offences (serial killing, homicide, sex crimes, weapon-related crimes, domestic violence, white-collar crimes, property crimes, drug-related crimes), recidivism (i.e., number of incarcerations), time spent in prison, and gender. Dimensionality and construct validity of the PPTS was investigated using traditional CFA techniques, confirmatory bifactor analysis, and multitrait-multimethod modelling (MTMM). Seven alternative models of the PPTS were estimated in Mplus using WLSMV estimator. An MTMM model with four grouping factors (affective responsiveness, cognitive responsiveness, interpersonal manipulation, and egocentricity) while controlling for two method factors (knowledge/skills and attitudes/beliefs) offered the best representation of the data. Good composite reliability and differential predictive validity was reported. The PPTS can be reliably used among prisoners from the United States.